Aggregation-fragmentation and individual dynamics of active clusters - F. Ginot (Nature Portfolio, 2018)
The cluster phase of active particles is one instance of the propensity of active matter to self-organize. Combining high-statistics experiments on Janus colloids and simple modeling, Ginot et al. provide a thorough characterization of cluster’s size and motion.